2017
DOI: 10.1111/pce.12884
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and control of nitric oxide generation by the plant mitochondrial electron transport chain

Abstract: The plant mitochondrial electron transport chain (ETC) is bifurcated such that electrons from ubiquinol are passed to oxygen via the usual cytochrome path or through alternative oxidase (AOX). We previously showed that knockdown of AOX in transgenic tobacco increased leaf concentrations of nitric oxide (NO), implying that an activity capable of generating NO had been effected. Here, we identify the potential source of this NO. Treatment of leaves with antimycin A (AA, Q -site inhibitor of Complex III) increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 91 publications
(116 reference statements)
1
29
0
Order By: Relevance
“…). Conversely, KD of AOX, which further reduces electron flow to oxygen when Complex III is inhibited (Alber et al ), enhanced the induction of these genes by AA, relative to WT (Fig. ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…). Conversely, KD of AOX, which further reduces electron flow to oxygen when Complex III is inhibited (Alber et al ), enhanced the induction of these genes by AA, relative to WT (Fig. ).…”
Section: Discussionmentioning
confidence: 91%
“…The MDGs identified by Maxwell et al () appear to respond in a relatively specific manner in tobacco leaf to the capacity for respiratory electron flow to oxygen. First, OE of AOX, which acts to maintain electron flow to oxygen when Complex III is inhibited (Alber et al ), largely blocked the induction of these genes by AA, relative to WT (Fig. ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…NO production by the plant mtETC is elevated under hypoxia (reviewed by Hebelstrup and Møller, 2015). Alber et al (2017) recently proposed that NO generation happens at complex III, while AOX dampens NO generation rate. Gibbs et al (2014) further showed that NO acts in the stabilization of RAP2.12, and this requires cytosolic nitrate reductase activity in vivo.…”
Section: Nitric Oxidementioning
confidence: 99%
“…Mitochondria are tightly linked to N metabolism and assimilation in plants (Szal and Podgórska, 2012) and is also a source of NO generated from nitrite and cytochrome c oxidoreductase activity in complex III (Alber et al, 2017). Additionally, NO was shown to be able to partially inhibit mitochondrial respiration (Gupta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%